ERP product selection criteria for Indian small and medium enterprises: an empirical study. (1st January 2013) - Garg, Poonam; Khurana, Reema
As competition is growing and the processes become more and more important in deciding the efficiency and bottom-line of small and medium scale enterprises (SME), the trend among SMEs to implement an appropriate ERP is catching up. Success of ERP implementation begins with selecting the right product to cater the need of all business types; inadequately selected ERP may affect companies' market share and implementation time, effort and cost. Selecting the right product can be extremely time-consuming and daunting. The research is therefore aimed at ERP product selection criteria for Indian SMEs. The finding of this research will help the marketing and sales team of ERP product companies to improve upon the key points and also enable end users to make informed decisions in selecting the ERP package for the organisation.